The Legal Protection for Digital Consumers in Game Diamond Purchase Transactions Online Mobile Legends - Zahrah Rani'ah Delyananda; Atik Winanti (Jurnal Daulat Hukum, 2025)
The development of digital technology is changing patterns of human interaction and transactions, including when purchasing virtual items like diamonds in the online game Mobile Legends. Digital agreements in these transactions require legal certainty in accordance with Article 1320 of the Civil Code and the Electronic Information and Transactions Law, especially if carried out by minors and/or through unofficial sellers. This study aims to examine the regulation of digital agreements between users and Mobile Legends game service providers in diamond purchase transactions, as well as to review legal protection for consumers (users), especially minors, who make diamond purchase transactions in Mobile Legends based on the Government to Business (G2B) Theory. The author uses a normative juridical research method with a statutory approach and a case approach related to illegal transactions in Langkat Regency. The research results show that transactions conducted outside official platforms do not meet the requirements of a valid electronic agreement and remove consumer protection rights as regulated in the UUPK and Government Regulation No. 80 of 2019. In conclusion, legal protection for digital consumers in purchasing game diamonds is still relatively weak. The government has not fully carried out its supervisory functions according to the G2B concept. To make the digital transaction ecosystem safer, fairer, and more accountable, stronger regulations, strict age verification systems, and firm sanctions for illegal business actors are needed.